2010
DOI: 10.2495/sc100461
|View full text |Cite
|
Sign up to set email alerts
|

Urban expansion and change of land uses: city of Mexicali 1990–2005

Abstract: Mexicali has an important economic role within the state of Baja California, Mexico, and its urban economic dynamic has been a central piece of regional development in the Mexicali valley. This has produced a rapid urbanization of the rural-urban interface, which has intensified energy, material and population exchanges between the central city and its hinterlands. Such a dynamic has produced urban sprawl and a fast restructuring of the urban regional spatial development. Thus, the purpose of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Satellite imagery is frequently used to analyze and document urban growth or model future urban growth [45,46]. For individual cities or transboundary cities along the area of interest, urban growth analyses using remote sensing include studies on Tijuana [47], Ciudad Juarez and El Paso [48], Mexicali [49], Agua Prieta, and Douglas [50]. No individual study on urban growth, sprawl, or expansion could be found for a few cities using remote sensing, including San Diego, Calexico, Ciudad Acuna, Del Rio, Piedras Negras, and Eagle Pass, San Luis Rio Colorado, or San Luis.…”
Section: Usage Of Aerial and Satellite Imagery For Measuring Urban Gr...mentioning
confidence: 99%
“…Satellite imagery is frequently used to analyze and document urban growth or model future urban growth [45,46]. For individual cities or transboundary cities along the area of interest, urban growth analyses using remote sensing include studies on Tijuana [47], Ciudad Juarez and El Paso [48], Mexicali [49], Agua Prieta, and Douglas [50]. No individual study on urban growth, sprawl, or expansion could be found for a few cities using remote sensing, including San Diego, Calexico, Ciudad Acuna, Del Rio, Piedras Negras, and Eagle Pass, San Luis Rio Colorado, or San Luis.…”
Section: Usage Of Aerial and Satellite Imagery For Measuring Urban Gr...mentioning
confidence: 99%
“…Thus, more attention should be paid to the drastic expansion of urbanization. Many studies have been conducted worldwide [1], including in regions of Africa [10], Europe [11], Latin America [12], North America [13], and Asia [14][15][16]. Previous studies have also explored the mechanisms of many cities, population and income related to urban and transforming in the process of modernization.…”
Section: Introductionmentioning
confidence: 99%